Distinct classes of lamina-associated domains are defined by differential patterns of repressive histone methylation - Martin, Caden J.; Oser, Elizabeth A.; Nagarajan, Prabakaran; Popova, Liudmila V.; Sunkel, Benjamin D.; Stanton, Benjamin Z.; Parthun, Mark R. (Genome Research, 2025)
A large fraction of the genome interacts with the nuclear periphery through lamina-associated domains (LADs), repressive regions which play an important role in genome organization and gene regulation across development. Despite much work, LAD structure and regulation are not fully understood, and a mounting number of studies have identified numerous genetic and epigenetic differences within LADs, demonstrating they are not a uniform group. Here, we profile lamin B1, CBX1 (also known as HP1B), H3K9me3, H3K9me2, H3K27me3, H3K14ac, H3K27ac, and H3K9ac in MEF cell lines derived from the same mouse colony, and cluster LADs based on the abundance and distribution of these features across LADs. We find that LADs fall into three groups, each enriched in a unique set of histone modifications and genomic features. Each group is defined by a different heterochromatin modification (H3K9me3, H3K9me2, or H3K27me3), suggesting that all three of these marks play important roles in regulation of LAD chromatin and potentially of lamina association. We also discover unique features of LAD borders, including a LAD border–specific enrichment of H3K14ac. These results reveal important distinctions between LADs and highlight the rich diversity and complexity in LAD structure and regulatory mechanisms.
10.1101/gr.280380.124